2015
DOI: 10.17988/0198-7429-41.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and Treating Stereotypical Behaviors in Classrooms Using a Functional Approach

Abstract: For years, the assumption has been that stereotypical behaviors functioned only to provide sensory or automatic reinforcement. However, these behaviors also may serve social functions. Given the unsettled debate, functional behavior assessment and functional analysis can be used to identify the exact function of stereotypical behavior and design an intervention matched to that function. In these two studies, we conducted functional behavior assessments on two high school students exhibiting stereotypical behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Implement Self-Monitoring. Selfmonitoring is an FABI component that can be effectively used to teach teachers and secondary students how to check their own behaviors (Bruhn et al, 2015;Bruhn & Watt, 2012). For example, Bruhn and Watt (2012) implemented a multicomponent self-monitoring intervention in an inclusive reading classroom with two middle school students.…”
Section: Increase Rates Of Crucial Proactive Behavioral Support Pract...mentioning
confidence: 99%
See 1 more Smart Citation
“…Implement Self-Monitoring. Selfmonitoring is an FABI component that can be effectively used to teach teachers and secondary students how to check their own behaviors (Bruhn et al, 2015;Bruhn & Watt, 2012). For example, Bruhn and Watt (2012) implemented a multicomponent self-monitoring intervention in an inclusive reading classroom with two middle school students.…”
Section: Increase Rates Of Crucial Proactive Behavioral Support Pract...mentioning
confidence: 99%
“…Within the context of secondary classrooms, crucial proactive behavioral support practices can improve behaviors (Flannery et al, 2013). In particular, we highlight the effective use of self-monitoring (Bruhn et al, 2015; Bruhn & Watt, 2012), delivery of behavior-specific praise (Ennis et al, 2020), and integration of student choices (Ennis, 2015) and preferences (Cooper et al, 2020) to reinforce appropriate behaviors.…”
Section: Strategies To Address Fabi Implementation Barriers In Second...mentioning
confidence: 99%
“…Teachers lack the time, resources, and knowledge to effectively implement an FBA and-despite their effectiveness with students with EBDsno amount of federal mandates requiring their use will improve the efficacy with which they are done in schools (Horner & Yell, 2017). It was encouraging then to see the five studies utilizing function-based interventions were implemented by practitioners rather than researchers (Bruhn et al, 2015;Forster et al, 2012;Hansen et al, 2014;Turton et al, 2011;Weeden et al, 2016). More studies documenting the means through which teachers can implement an FBA may increase their use in schools.…”
Section: Common Interventionsmentioning
confidence: 99%
“…For instance, a review of over 500 studies of various prevention and intervention programs indicated that effects were 2 to 3 times greater when programs were implemented with integrity (Durlak & DuPre, 2008). Conversely, failure to consistently implement all components indicates a lack of fidelity and could result in the desired changes not occurring (Bruhn et al, 2015). In addition, if interventions are not implemented with fidelity, inaccurate conclusions about the student’s responsiveness may be made.…”
Section: Assessment and Intervention Fidelitymentioning
confidence: 99%
“…In addition to fidelity checks completed by an outside observer, self-monitoring of fidelity by the interventionist is another way to increase accurate implementation. In a study of an FBA-derived BIP for a student with stereotypical behavior, the implementing teacher improved her use of behavior-specific praise when she monitored her own use of praise, which in turn resulted in improved student behavior (Bruhn et al, 2015). In a related way, interventionists can complete the same fidelity forms.…”
Section: Additional Recommendations For Improving Overall Fidelitymentioning
confidence: 99%